Chapter Leonardo e la navigabilità dei corsi d'acqua milanesi - Candia, Claudia (Territori, 2023)
The paper analyses Leonardo's main studies concerning the navigability of Milan waterways in order to contextualize and highlight his original contributions. Not only do Leonardo's studies outline the actual situation of such waterways, they also include new projects and innovations. Even though these are not always ascribable to Leonardo, he certainly drew and examined them himself. The analysis is based on the study of the main transformations of Milan water system and territory over the centuries.